Factors delaying mobilization after hip and knee arthroplasty - Hafeez, Kamran; Umar, Muhammad; Desai, Vikram (International Journal of Health Sciences, 2024)
Objective: Arthroplasty patients undergo pre-operative assessment and medical optimization before surgery with the objective to mobilize and discharge home as soon as deemed fit to reduce hospital stay. This study was aimed to investigate factors delaying mobilization after hip and knee arthroplasty in our hospital. Methods: This observational study was conducted in our hospital between August 2021 and October 2021. We included all elective orthopedic patients who were admitted for hip and knee arthroplasty during this period. Patients admitted for revision arthroplasty were excluded from the study. We collected data prospectively on a pro forma including patient demographics and different other variables. All patients were reviewed on the first post-operative day by one of the authors and pro formas were completed. We used SPSS to analyze data. Results: Sixty patients were included; 32 females and 28 males with a mean age of 69.62 years. Primary knee arthroplasty was done in 30 patients while 30 underwent primary hip arthroplasty. Most of the patients (n = 50) were mobilized on the 1st day; however, ten patients were unable to mobilize. Orthostatic hypotension, dizziness, and pain were statistically significant factors responsible for failed mobilization on day one. Patients who failed to mobilize on day one had longer hospital stay (P = 0.018). Conclusion: Orthostatic intolerance and post-operative pain were independent factors delaying mobilization after hip and knee arthroplasty thereby increasing the length of stay in these patients.